Episodes of Rapid Recovery of the Functional Activity of the ras85D Gene in the Evolutionary History of Phylogenetically Distant Drosophila Species - Chekunova, A. I.; Sorokina, S. Yu.; Sivoplyas, E. A.; Bakhtoyarov, G. N.; Proshakov, P. A.; Fokin, A. V.; Melnikov, A. I.; Kulikov, A. M. (Frontiers in Genetics, 2022)
Structural rearrangements of the regulatory region of the ras85D gene can lead to the formation of lethal or severely deleterious alleles. In nature, such alleles can only be preserved exclusively in heterozygotes and then should be quickly lost due to selection and genetic drift. Analysis of the variability of the regulatory region of the ras85D gene and its orthologues performed on 37 drosophila species with varying phylogenetic relationships of two subgenera: Drosophila and Sophophora, revealed that structural rearrangements in the ras85D regulatory region leading to a complete replacement of the promoter, the transcription start site (TSS) and the entire regulatory region of the gene occurred multiple times in the evolutionary history of different groups of Drosophila. The studied model is characterized by a strictly functional and structural conservativity of the protein encoded by the gene and the lethal nature of null-alleles, which forbid gene expression. The detected structural changes in the regulatory region sequense are presumably associated with insertions of mobile elements and, in some cases, with the chromosomal rearrangements. The significant changes of functionaly important elements, such as replacement of promoter or reshuffle of regulatory region of the gene should have been accompanied by the restoration of its functional activity for a limited number of generations. A set of evolutionary-conservative sequences that are present in different positions and on different DNA strands in most species, and could take over the function of a damaged or lost element, was determined in the intergenic spacer, 5'UTR and Intron 1 of the ras85D gene of different Drosophila species. A possible recovery mechanism for restoring the functional activity of the gene after structural changes in the regulatory region is a random selection of the appropriate composition of potential promoter elements and conversion of sequence fragments containing sites, which are significant for the regulation of expression.